2023
DOI: 10.3390/microorganisms11020493
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia amblyommatis in Ticks: A Review of Distribution, Pathogenicity, and Diversity

Abstract: Rickettsia amblyommatis is a potentially pathogenic species of Rickettsia within the spotted fever group vectored by ticks. While many studies have been published on this species, there is debate over its pathogenicity and the inhibitory role it plays in diagnosing illnesses caused by other spotted fever group Rickettsia species. Many publications have recorded the high infection prevalence of R. amblyommatis in tick populations at a global scale. While this species is rather ubiquitous, questions remain over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 200 publications
1
11
0
Order By: Relevance
“…In Maranhão, R. amblyommatis is frequent in A. cajennense s.s. populations, with infection rates ranging from 1 to 16.7%, corroborating our results [53]. It is important to mention that R. amblyommatis is potentially pathogenic to humans [29], but its association with clinical cases of spotted fever rickettsiosis in humans and animals is unclear. Interestingly, it has been shown that R. amblyommatis infection may prevent ticks from acquiring other species of Rickettsia, may alter tick host-seeking behavior and also in uence the progression of disease symptoms when infecting humans [29].…”
Section: Cabrera and Labrunasupporting
confidence: 88%
See 1 more Smart Citation
“…In Maranhão, R. amblyommatis is frequent in A. cajennense s.s. populations, with infection rates ranging from 1 to 16.7%, corroborating our results [53]. It is important to mention that R. amblyommatis is potentially pathogenic to humans [29], but its association with clinical cases of spotted fever rickettsiosis in humans and animals is unclear. Interestingly, it has been shown that R. amblyommatis infection may prevent ticks from acquiring other species of Rickettsia, may alter tick host-seeking behavior and also in uence the progression of disease symptoms when infecting humans [29].…”
Section: Cabrera and Labrunasupporting
confidence: 88%
“…It is important to mention that R. amblyommatis is potentially pathogenic to humans [29], but its association with clinical cases of spotted fever rickettsiosis in humans and animals is unclear. Interestingly, it has been shown that R. amblyommatis infection may prevent ticks from acquiring other species of Rickettsia, may alter tick host-seeking behavior and also in uence the progression of disease symptoms when infecting humans [29]. Altogether, these data emphasize the importance of further studies on this rickettsial organism.…”
Section: Cabrera and Labrunamentioning
confidence: 99%
“…DNA sequences were successfully generated for seven out of 33 ompA -PCR positive ticks, all of which assigned to R. amblyommatis . This bacterium has been detected in 34 tick species in 17 American countries [ 29 ]. The infection rate in ticks can exceed 90% in the USA, Panama and Brazil, with approximately 70% of natural infection for the Amazon biome [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A. cajennense s.s. ticks are often infected (20–26%) by Rickettsia amblyommatis (formerly ‘ Candidatus Rickettsia amblyommii ’), which is successfully maintained by transovarial and transstadial transmission [ 28 ]. While there is little information on R. amblyommatis infections in animals and humans, its role as a causative agent of spotted fever in humans cannot be ruled out [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rickettsia amblyommatis has gained attention in recent years due to its suspected pathogenicity [ 51 ]. Some authors hypothesize that this species’ pathogenicity might be different across strains, whereas others suggest it has a role as a tick endosymbiont, which could explain its wide geographical distribution [ 52 , 53 ]. In Colombia, R. amblyommatis has been detected molecularly among A. cajennense s.l.…”
Section: Molecular Evidencementioning
confidence: 99%